Causal Relationships Between Blood Lipid Levels and Chronic Obstructive Pulmonary Disease: A Mendelian Randomization Analysis - Huang P; Zhao Y; Wei H; Wu W; Guo Z; Ma S; Xu M; Wang Q; Jia C; Xiang T; Li H (International Journal of COPD)
Ping Huang,* Yong Zhao,* Haiyan Wei, Wenhui Wu, Ziwen Guo, Shiyi Ma, Meng Xu, Qin Wang, Cheng Jia, Ting Xiang, Huamao Li Department of Rehabilitation Medicine, General Hospital of Central Theater Command, Wuhan, 430065, People’s Republic of China*These authors contributed equally to this workCorrespondence: Huamao Li; Ting Xiang, Department of Rehabilitation Medicine, General Hospital of Central Theater Command, Wuhan, 430065, People’s Republic of China, Email 71831102@qq.com; 42254403@qq.comBackground: In preliminary research and literature review, we identified a potential link between chronic obstructive pulmonary disease (COPD) and lipid metabolism. Therefore, this study employed Mendelian randomization (MR) analysis to investigate the potential causal connection between blood lipids and COPD.Materials and Methods: A genome-wide association study (GWAS) on COPD was conducted, encompassing a total of 112,583 European participants from the MRC-IEU. Additionally, extensive UK Biobank data pertaining to blood lipid profiles within European cohorts included measurements for low-density lipoprotein cholesterol (LDL-C) with 440,546 individuals, high-density lipoprotein cholesterol (HDL-C) with 403,943 individuals, triglycerides (TG) with 441,016 individuals, total cholesterol (TC) with 187,365 individuals, apolipoprotein A-I (apoA-I) with 393,193 individuals, and apolipoprotein B (apoB) with 439,214 individuals. Then, MR analyses were performed for lipids and COPD, respectively. The primary analytical technique employed was the inverse-variance weighted (IVW) approach, which included a 95% confidence interval (CI) to calculate the odds ratio (OR). Additionally, a sensitivity analysis was conducted to assess the dependability of the MR analysis outcomes.Results: MR analysis was primarily based on IVW, unveiled a causal link between COPD and LDL-C (OR=0.994, 95% CI (0.989, 0.999), P=0.019), TG (OR=1.005, 95% CI (1.002, 1.009), P=0.006), and apoA-I (OR=0.995, 95% CI (0.992, 0.999), P=0.008), in addition, no causal link was found with HDL-C, TC, apoB. Sensitivity analysis demonstrated the robustness of these causal relationships. However, through multivariate MR(MVMR) and multiple testing correction, LDL-C and TG had no causal effect on the outcome. ApoA-I remained a protective factor for the risk of COPD (OR=0.994, 95% CI (0.990– 0.999), P=0.008).Conclusion: Through MR analysis, this study offers evidence of a causal link between apoA-I with COPD. This further substantiates the potential role of lipid metabolism in COPD, and has significant clinical implications for the prevention and management of COPD.Keywords: lipid metabolism, COPD, Mendelian randomization analysis, apolipoprotein A-I